KREATIVITAS GURU AL- QURAN HADIST DALAM MENGEMBANGKAN BAHAN AJAR DI MADRASAH ALIYAH NEGERI 1 TANJUNG JABUNG BARAT - Asmarita Saputri; Ahmad Ridwan; Siti Raudhatul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The thesis research is motivated by the importance of teacher creativity in developing effective and efficient teaching materials, specifically for Quran Hadith learning at Madrasah Aliyah Negeri 1 Tanjung Jabung Barat. Quality teaching materials must be able to improve learning outcomes, motivate students, strengthen material retention, and activate students in applying knowledge and skills. This is caused by several problems such as a lack of variation in teaching materials, low teacher creativity in integrating learning sources, and limited innovation which impacts low student activeness and comprehension. This study aims to analyze: first, the creativity of Quran Hadith teachers in developing teaching materials; second, the types of teaching materials used by the teachers; and third, the inhibiting and supporting factors of teacher creativity. The study uses a qualitative approach with a descriptive method, which involves describing field facts through observation, interviews, and documentation, then analyzing them based on the research variables. The results show that the creativity of the Quran Hadith teachers is reflected in their ability to utilize technology like laptops and projectors in designing digital-based teaching materials, creating modules, compiling core material, evaluation questions, and designing interactive quizzes. Teachers also demonstrate creative thinking ability through aspects of thinking fluency, flexibility, originality, and elaboration. The teaching materials used are combinative, including print materials, digital materials, and materials resulting from the teacher's own creativity. The use of diverse teaching materials provides a more interesting and relevant learning experience for students. Inhibiting factors for teacher creativity include time constraints, minimal facilities and infrastructure, administrative burden, and the teacher's technological skills. Meanwhile, supporting factors include teacher competency, availability of facilities, madrasah support, and a conducive work environment. This research asserts that teacher creativity plays a crucial role in improving the quality of Quran Hadith learning and needs to be continuously enhanced through teacher support and professional development.